2021 IEEE International Humanitarian Technology Conference (IHTC) 2021
DOI: 10.1109/ihtc53077.2021.9698969
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transition X Energy Inclusion: A Community Energy Concept for Developing Countries

Abstract: The concept of community energy has gained acceptance and popularity within academic and scientific communities, in addition to public debate forums. Community energy drives socio-economic transformations, as it places the citizen and the community as the main actors in the entire energy value chain, based on the principle of local and autonomous generation of energy by and for the community. In this article, we analyze the socio-economic impact of community energy as a strategy for energy inclusion and partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The status of full access to energy sources in developing countries allows a progressive transformation and development of the energy sector, giving rise to the concept of CE, where the citizen and the community are no longer simple customers [3]- [5]. In the CE concept, energy is produced by and for the community, placing the citizen and the community as main actors in the energy value chains (generation, distribution, consumption and services) and aiming at energy autonomy, socioeconomic empowerment and human development of local community [6].…”
Section: A Context Of the Search Problemmentioning
confidence: 99%
“…The status of full access to energy sources in developing countries allows a progressive transformation and development of the energy sector, giving rise to the concept of CE, where the citizen and the community are no longer simple customers [3]- [5]. In the CE concept, energy is produced by and for the community, placing the citizen and the community as main actors in the energy value chains (generation, distribution, consumption and services) and aiming at energy autonomy, socioeconomic empowerment and human development of local community [6].…”
Section: A Context Of the Search Problemmentioning
confidence: 99%
“…Another study examined the impact of community energy as a strategy for energy inclusion and participation in industrial, socioeconomic and human development in developing countries, particularly in sub-Saharan Africa. The study found that community energy promotes socio-economic transformation, as it places citizens and communities as key actors in the entire energy value chain, based on the principle of local and autonomous energy generation by and for communities [9]. Furthermore, a study conducted in Indonesia examined the scarcity of palm oil as a CPO food commodity and the government's conservative measures through green resolution policies and strengthening local value chains.…”
Section: Introductionmentioning
confidence: 99%